1990
DOI: 10.1111/j.1365-2494.1990.tb01949.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of herbage water‐soluble carbohydrate content and weather conditions at ensilage on the fermentation of grass silages made on commercial farms

Abstract: A total of 1009 samples of silage made in bunker silos on commercial farms between 1972 and 1978 was analysed to investigate the effect of herbage water‐soluble carbohydrate content (WSC) and weather conditions at ensilage on fermentation as measured by ammonia‐N concentration and pH of first‐cut grass silages. Silage dry matter (DM) content had the major effect on fermentation. Factors influencing silage DM were rainfall and hours of sunshine during silage making, and DM content of the grass cut. WSC content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1
6

Year Published

1998
1998
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 7 publications
1
46
1
6
Order By: Relevance
“…McCullough (1977) recommended soluble carbohydrate contents greater than 80 g/kg of the dry matter and moisture content close to 700 g/kg as potential for ensilage of a plant. However, Haigh (1990) suggested that there was an inverse relation between the need for sugars and the dry matter content of the forage to obtain proper fermentation. Van Soest (1994) reported that the SC: buffering capacity ratio should be high, to obtain good-quality silage, if the dry matter content of the forage is reduced.…”
Section: Resultsmentioning
confidence: 99%
“…McCullough (1977) recommended soluble carbohydrate contents greater than 80 g/kg of the dry matter and moisture content close to 700 g/kg as potential for ensilage of a plant. However, Haigh (1990) suggested that there was an inverse relation between the need for sugars and the dry matter content of the forage to obtain proper fermentation. Van Soest (1994) reported that the SC: buffering capacity ratio should be high, to obtain good-quality silage, if the dry matter content of the forage is reduced.…”
Section: Resultsmentioning
confidence: 99%
“…Os carboidratos solúveis são o mais importante substrato para boa fermentação da forragem. O conteúdo de carboidratos solúveis de uma forrageira é considerado com um parâmetro indicador da qualidade da forragem para ensilagem, sendo necessária uma concentração mínima de 2,5 a 3,0% na MS (HAIGH, 1990). Segundo o mesmo autor, existe uma relação inversa entre a necessidade de carboidratos solúveis e o teor de matéria seca da forragem para que ocorra uma boa fermentação.…”
Section: Introductionunclassified
“…In contrast, the addition of rice bran to chopped elephant grass resulted in a significant linear increase (P < 0.05) in the WSC content of material, with a 0.177% increase for every 1% of rice bran added (Table 1). The WSC content is considered an indicator of the quality of the forage to be used for ensiling, with a minimum concentration of 2.5 to 3.0% required (HAIGH, 1990). Despite some elephant grass cultivars possessing a WSC content greater than 16% of DM (Taiwan A-148), reasonable silages have been produced when the cultivar used has a WSC content below 13% to 15%.…”
Section: Resultsmentioning
confidence: 99%